Efektivitas Implementasi Kurikulum Merdeka Belajar di Tingkat Sekolah Menengah Atas : Tinjauan Psikologis dan Struktural - Neva Lionitha Ibrahim; Nurlinda Yunus; Rahmatia J. Lopuo (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to evaluate the effectiveness of the implementation of the Independent Learning Curriculum at the Senior High School level by focusing on the psychological aspects of students and factors that hinder implementation. Data were obtained from two case studies at SMAN 3 Gorontalo and SMAN 1 Telaga Biru through a qualitative descriptive method with interview, observation, and documentation techniques. The results of the study show that the Independent Curriculum has a positive impact on the psychological development of students, especially in three main aspects, namely cognitive, affective, and psychomotor. Students demonstrate improved critical thinking skills, learning motivation, and practical skills through project-based learning. However, the implementation of this curriculum is also faced with various internal obstacles such as low motivation and interest of students, as well as lack of discipline due to freedom in the learning process. External barriers include limited school facilities, lack of parental support for the results of interest-talent assessments, and low teacher readiness and competence in understanding and implementing the curriculum. Based on these findings, systemic support from the government, schools, teachers, and parents is needed to optimize the implementation of the Independent Curriculum so that the goals of national education can be achieved comprehensively.